Fuel consumption and air emissions in one of the world's largest commercial fisheries. (15th March 2021) - Chassot, Emmanuel; Antoine, Sharif; Guillotreau, Patrice; Lucas, Juliette; Assan, Cindy; Marguerite, Michel; Bodin, Nathalie
Abstract: The little information available on fuel consumption and emissions by high seas tuna fisheries indicates that the global tuna fleet may have consumed about 2.5 Mt of fuel in 2009, resulting in the production of about 9 Mt of CO2 -equivalent greenhouse gases (GHGs), i.e., about 4.5–5% of the global fishing fleet emissions. We developed a model of annual fuel consumption for the large-scale purse seiners operating in the western Indian Ocean as a function of fishing effort, strategy, and vessel characteristics based on an original and unique data set of more than 4300 bunkering operations that spanned the period 2013–2019. We used the model to estimate the total fuel consumption and associated GHG and SO2 emissions of the Indian Ocean purse seine fishery between 1981 and 2019. Our results showed that the energetic performance of this fishery was characterized by strong interannual variability over the last four decades. This resulted from a combination of variations in tuna abundance but also changes in catchability and fishing strategy. In recent years, the increased targeting of schools associated with fish aggregating devices in response to market incentives combined with the IOTC management measure implemented to rebuild the stock of yellowfin tuna has strongly modified the productivity and spatio-temporal patterns of purse seine fishing. This had effects on fuel consumption and air pollutant emissions. Over the period 2015 to 2019, the purse seine fishery, including its support vessel component, annually consumed about 160, 000 t of fuel and emitted 590, 000 t of CO2-eq GHG. Furthermore, our results showed that air pollutant emissions can be significantly reduced when limits in fuel composition are imposed. In 2015, SO2 air pollution exceeded 1500 t, but successive implementation of sulphur limits in the Indian Ocean purse seine fishery in 2016 and 2018 have almost eliminated this pollution. Our findings highlight the need for a routine monitoring of fuel consumption with standardized methods to better assess the determinants of fuel consumption in fisheries and the air pollutants they emit in the atmosphere. Graphical abstract: Image 1 Highlights: We modelled the annual fuel consumption in tuna purse seiners of the Indian Ocean. Days at sea, numbers of operations, vessel length and age affect fuel consumption. Fuel Use Intensity and consumption showed strong variability over 1981 to 2019. Greenhouse gas emissions were about 600, 000 t y −1 of CO2 -eq over 2015 to 2019. Sulphur limits reduced annual SO2 emissions from >1500 t to almost none since 2018.